Efektivitas Penanganan DP3AP2KB Dalam Mengatasi Kekerasan Terhadap Perempuan Dan Anak Di Kabupaten Merauke - Bhodo, Agustinus Esra; Betaubun, Restu Monika Nia; Kalalo, Julianto Jover Jotam (Universitas Musamus, 2024)
Violence is defined as behavior by a person or group that harms a person's bodily or mental integrity. Children and women victims of violence in Merauke Regency are increasingly concerned, most victims experience physical and psychological abuse. Economic demands are one of the main causes of violence. The purpose of this paper is to find out how the effectiveness of DP3AKB Merauke Regency, against violence against women and children in Merauke Regency. The qualitative method used by researchers in this writing. While the case approach used in this writing. Based on the author's analysis, effective steps in women's empowerment, child protection, and family planning are instrumental in helping women and children in Merauke Regency in order to overcome violence. To carry out a prevention, recovery, and resocialization in handling violence against women and children is certainly a serious challenge faced, this is because there is a habit in society that thinks that violence against children and women is a disgrace forbidden for families and schools.To ensure protection for victims can run properly, victims and psychologists must communicate in advance during recovery efforts so that these problems can be addressed, especially in terms of trauma caused by the violence.